SISTEM PENDUKUNG KEPUTUSAN DALAM MENENTUKAN JUMLAH PERSEDIAN STOK OBAT DENGAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Indah Melati; Hartono Hartono (Sienna, 2023)
A pharmacy is a location where pharmaceutical activities are carried out and the distribution of drugs to the public. This research focuses on the problem of managing drug inventory at Arto Moro Pharmacy, which is based on the need for an efficient decision support system in determining the optimal amount of drugs. Issues such as drugs that are no longer suitable for use and waste require a more efficient management system. The purpose of this research is to develop a decision support system using the Simple Additive Weighting (SAW) method to overcome these problems. The SAW method is used to handle problems in complex decision-making by combining relevant criteria and giving an assessment of each criterion. The research results consist of four main stages: the creation of a decision matrix from drug demand and supply data, the creation of a decision matrix for each type of drug, the calculation of rankings by summing the criteria matrix, and the determination of the amount of inventory for May by considering the final value in the form of a percentage of the previous moth’s demand (April). The application of the SAW method has succeeded in creating an effective decision support system in determining the amount of drug inventory at Arto Moro Pharmacy. The results of this study provide an in-depth understanding of the application of the SAW method in drug inventory management in pharmacies, which contributes to addressing the problem of efficiency.